Modeling of pathogenic variants of mitochondrial DNA polymerase: insight into the replication defects and implication for human disease - Hoyos-Gonzalez, Nallely; Trasviña-Arenas, Carlos H.; Degiorgi, Andrea; Castro-Lara, Atzimaba Y.; Peralta-Castro, Antolín; Jimenez-Sandoval, Pedro; Diaz-Quezada, Corina; Lodi, Tiziana; Baruffini, Enrico; Brieba, Luis G. (Biochimica et biophysica acta. General subjects, 2020)
Mutations in human gene encoding the mitochondrial DNA polymerase γ (HsPolγ) are associated with a broad range of mitochondrial diseases. Here we studied the impact on DNA replication by disease variants clustered around residue HsPolγ-K1191, a residue that in several family-A DNA polymerases interacts with the 3′ end of the primer. Specifically, we examined the effect of HsPolγ carrying pathogenic variants in residues D1184, I1185, C1188, K1191, D1196, and a stop codon at residue T1199, using as a model the yeast mitochondrial DNA polymerase protein, Mip1p. The introduction of pathogenic variants C1188R (yV945R), and of a stop codon at residue T1199 (yT956X) abolished both polymerization and exonucleolysis in vitro. HsPolγ substitutions in residues D1184 (yD941), I1185 (yI942), K1191 (yK948) and D1196 (yD953) shifted the balance between polymerization and exonucleolysis in favor of exonucleolysis. HsPolγ pathogenic variants at residue K1191 (yK948) and D1184 (yD941) were capable of nucleotide incorporation albeit with reduced processivity. Structural analysis of mitochondrial DNAPs showed that residue HsPolγ-N864 is placed in an optimal distance to interact with the 3′ end of the primer and the phosphate backbone previous to the 3′ end. Amino acid changes in residue HsPolγ-N864 to Ala, Ser or Asp result in enzymes that did not decrease their polymerization activity on short templates but exhibited a substantial decrease for processive DNA synthesis. Our data suggest that in mitochondrial DNA polymerases multiple amino acids are involved in the primer-stand stabilization. •Residue K1191 in polymerases homologous to human DNA polymerase gamma is poised to interactswith the 3′ end of the primer.•Amino acid variants near residue K1191 favors exonucleolysis.•Our data suggest that multiple amino acids could be involved in the primer-stand stabilization.